Manufacturing and investigation of physical properties of polyacrylonitrile nanofibre composites with SiO2, TiO2 and Bi2O3 nanoparticles - Tański, Tomasz; Matysiak, Wiktor; Hajduk, Barbara (Beilstein Journal of Nanotechnology, 2016)
The aim of this study was to produce nanocomposite polymer fibres, consisting of a matrix of polyacrylonitrile (PAN) and a reinforcing phase in the form of SiO2/TiO2/Bi2O3 nanoparticles, by electrospinning the solution. The effect of the nanoparticles and the electrospinning process parameters on the morphology and physical properties of the obtained composite nanofibres was then examined. The morphology of the fibres and the dispersion of nanoparticles in their volume were examined using scanning electron microscopy (SEM). All of the physical properties, which included the band gap width, dielectric constant and refractive index, were tested and plotted against the concentration by weight of the used reinforcing phase, which was as follows: 0%, 4%, 8% and 12% for each type of nanoparticles. The width of the band gap was determined on the basis of the absorption spectra of radiation (UV–vis) and ellipsometry methods. Spectroscopic ellipsometry has been used in order to determine the dielectric constant, refractive index and the thickness of the obtained fibrous mats.
Keywords: ceramic nanoparticles; electrospinning methods; polyacrylonitrile; polymer composite nanofibres; spectroscopic ellipsometry